Guatemala : 2009 Article IV Consultation and Second Review Under the Stand-By Arrangement, and Requests for Modification of Performance Criterion and Consultation Clause-Staff Report; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Guatemala. (IMF Staff Country Reports; Country Report ;, 2010)
The staff report on Guatemala's 2009 Article IV Consultation and Second Review under the Stand-By Arrangement, and Requests for Modification of Performance Criterion and Consultation Clause are presented. There are signs that the Guatemalan economy is starting to recover. Real GDP growth and inflation are picking up, imports have begun to grow, and net private capital flows have stabilized. Real GDP growth is likely to remain low and inflation subdued. Over the medium term, economic growth is expected to be weaker than prior to the global crisis, and inflation to stabilize at trading partners' levels.